PEDAGOGICAL CONDITIONS OF FORMATION OF THE READINESS OF FUTURE MASTERS OF PRIMARY EDUCATION FOR INNOVATION ACTIVITY - Popovych, Ihor; Tsiuniak, Oksana; Machynska, Natalia; Bokshan, Halyna; Aleksieieva, Mariia; Los, Oksana; Sultanova, Leila (Revista Inclusiones, 2020)
The article focuses on the importance of pedagogical conditions in forming the readiness of future masters of primary education for innovations in higher education institutions. The purpose of the article is to substantiate and test the pedagogical conditions for forming the readiness of future masters of primary education for innovation activity on the basis of generalization of theoretical and practical principles of their professional training. The pedagogical conditions of forming the readiness of future masters of primary education for innovation activity in the process of their professional training are substantiated and characterized: the formation in the future masters of primary education values-based attitude to professional activity; activation of positive motivation of graduate students for innovation activity, taking into account an innovative educational environment of a higher education institution; substantiation of the content, forms, methods and means of professional training of future masters of primary education for innovations in higher education institutions; creative implementation of innovative technologies in the educational process, aimed at forming the readiness of future masters of primary education for innovations. The influence of certain pedagogical conditions on the formation of the readiness of future masters of primary education for innovation activity is determined.